Isolation and characterization of mesenchymal stem cells derived from dental pulp and follicle tissue of human third molar tooth - Yadegary Z; Mojarrad S; Mashadi Abbas F; Sharifi B (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: In the last decade, several studies have reported the isolation of stem cell population from different dental sources, while their mesenchymal nature is still controversial. The aim of this study was to isolate stem cells from mature human dental pulp and follicle and to determine their mesenchymal nature before differentiation based on the ISCT (International Society for Cellular Therapy) criteria."nMaterials and Methods: In this experimental study, intact human third molars extracted due to prophylactic or orthodontic reasons were collected from patients aged 18-25. After tooth extraction, dental pulp and follicle were stored at 4°C in RPMI 1640 medium containing antibiotics. Dental pulp and follicle were prepared in a sterile condition and digested using an enzyme solution containing 4mg/ml collagenase I and dispase (ratio: 1:1). The cells were then cultivated in α-MEM medium. Passage-3 cells were analyzed by flow cytometry for the expression of CD34, CD45, CD 73, CD90 and CD105 surface markers."nResults: Dental pulp and follicle were observed to grow in colony forming units, mainly composed of a fibroblast-like cell population. Flow cytometry results showed that dental pulp and follicle are highly positive for CD73, CD90 and CD105 (mesenchymal stem cell markers) and are negative for hematopoietic markers such as CD34 and CD 45."nConclusion: In this study we were able to successfully confirm that dental pulp and follicle stem cells isolated from permanent third molars have a mesenchymal nature before differentiation. Therefore, these two sources can be considered as an easy accessible source of mesenchymal stem cells for stem cell research and tissue engineering.